Mindfulness Based Stress Reduction (MBSR) Technique Intervention to Reduce Students' Academic Stress - Fadil Maiseptian; Rani Desmaniar; Thaheransyah Thaheransyah; Murisal Murisal; Akmil Rahmi; Nurwinda Sulistyawati (Universitas PGRI Yogyakarta, 2026)
This study was motivated by the increasing prevalence of academic stress among students at an Islamic Junior High School in Padang. Although Mindfulness-Based Stress Reduction (MBSR) has been widely demonstrated to be effective across various educational and clinical settings worldwide, its application within faith-based educational environments, particularly Islamic madrasas in Indonesia, remains limited and underexplored. Accordingly, this study offers a novel contribution by examining the implementation of MBSR in the context of Islamic lower secondary education. The research aimed to investigate the effectiveness of MBSR in reducing students’ academic stress levels. A quantitative approach was employed using a pre-experimental one-group pretest–posttest design. The participants consisted of 31 eighth-and ninth-grade students selected through purposive sampling based on high levels of academic stress. The MBSR intervention was delivered through structured sessions incorporating core components such as body scan, sitting meditation, and mindful breathing. Academic stress was measured using a Likert-scale questionnaire that demonstrated satisfactory validity and reliability (adequate Cronbach’s Alpha). Data were analyzed using the Wilcoxon Signed-Rank Test. The findings revealed a statistically significant reduction in academic stress (Z = −4.862; p < 0.001) with a large effect size. These results support the integration of mindfulness-based interventions into school counseling services within faith-based educational settings. Keywords: academic stress, mindfulness-based stress reduction (MBSR), psychological intervention